“Masha,” a Story by B.K. Zaitsev: Composition and Idea of Order of Estate Life - Valeria G. Andreeva (Studia Litterarum)
The article comprehends the structure of the story by B.K. Zaitsev’s “Masha” (1915) as a parallel development and non-linear comparison of two storylines dedicated to the love stories of the noblewoman Lisa and her peer, the peasant girl Masha. The author of this article explained the writer’s choice of the story’s title (after the name of the peasant heroine, which marks the semiotic shifts in the “estate culture” of the Silver Age). The article examines in detail the dichotomy of order / disorder, which substantially organizes the artistic world of the work. The research explores the ways of representing the “estate topos” and analyses the sociocultural connection of the heroines with the estate. The Kochki and Radishchevo estates described in the story are also characterized as two varieties of “estate topos” in Russian literature at the turn of the 19th–20th centuries. There is a typological similarity between Liza Andreeva in Zaitsev’s story “Masha” and Liza Kalitina in the novel by I.S. Turgenev, Home of the Gentry (1858). It indicates Zaitsev’s reception of Turgenev’s characterological principles in the dual portrayal of the heroines. The article identifies and classifies the details of everyday estate life in Zaitsev’s story and highlights the author’s complex, ambiguous attitude towards characters leading a secluded estate existence.